146k views
0 votes
I need Help on 8 or both (if possible)

I need Help on 8 or both (if possible)-example-1
User Deron
by
5.8k points

1 Answer

1 vote

I only see one question here...

If
y=f(x) is a one-to-one function, then it has an inverse such that
f^(-1)(y)=x. This means that
f^(-1)(f(x))=x.

According to the table,
f(1)=-2. So by definition of the inverse, we have


f(1)=-2\implies f^(-1)(f(1))=f^(-1)(-2)\implies\boxed{1=f^(-1)(-2)}

so the answer is either B or D (they're both the same...)

User Dianakarenms
by
5.5k points